The Discourse of The Qur'anic Metaphors: The Embryo of Theological Sects Disputes in Comprehending the Holy Qur'an - Ahmad Atabik (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This article aims to examine problems related to metaphors (majāz) found in the Qur’an which were debated by scholars of Arabic literatures during the classic times. Majāz, opposed to ḥaqīqah, is a part of the Qur'an language styles which triggers theological debates among its supporters. This article used a qualitative approach, through library research, with a comprehensive and comparative analysis method among supporters of theological sects in understanding the problems of majāz in the Qur'an. The results of this study indicated that the debates on the issue raises three opinions in theological sects; Firstly, the Ẓahirī and Salafi sects reject the existence of majāz in the Qur'an. They refuse the interpretations of things that are not standardized in the text of the Qur'an. Secondly, the Mu'tazilah sect is exaggerated in accepting majāz and attacking other theological sects that are inconsistent with their interpretations of the text. Thirdly, the Ash’arī sect which is more moderate in confirming majāz. The starting point of their debates over majāz in the Qur'an is the difference in analysis and conclusions about the origin of language. The Ẓahirī and Salafi groups conclude that language is solely a gift from God, so there should be no change in terms of meaning. The Mu'tazilah believes that language is an invention and human power, that’s why a word may have more than one meaning. Whilst, the Ash’arī argues that language is indeed a human creativity, but it cannot be denied that God also plays a role in giving human abilities, so there are other possible meanings of a word